A comparative study of stress episode prevalence and duration among jomon period foragers from hokkaido. Issue 2 (31st August 2013) - Temple, Daniel H.; McGroarty, Jennifer N.; Guatelli‐Steinberg, Debbie; Nakatsukasa, Masato; Matsumura, Hirofumi
ABSTRACT This study reconstructs linear enamel hypoplasia (LEH) prevalence and stress episode duration among Jomon period foragers from Hokkaido, Japan (HKJ). Results are compared to Jomon period samples from coastal Honshu, Japan (HSJ) and Tigara Inupiat from Point Hope, Alaska (PHT) to provide a more comprehensive perspective on the manifestation of stress among circum‐Pacific foragers. LEH were identified macro‐ and microscopically by enamel surface depressions and increased perikymata spacing within defects. Individuals with more than one anterior tooth affected by LEH were labeled as LEH positive. Stress episode durations were estimated by counting the number of perikymata within the occlusal wall of each LEH and multiplying that number by constants reflecting modal periodicities for modern human teeth. LEH prevalence and stress episode duration did not differ significantly between the two Jomon samples. Significantly greater frequencies of LEH were found in HKJ as compared to PHT foragers. However, HKJ foragers had significantly shorter stress episode durations as compared to PHT. This suggests that a greater proportion of HKJ individuals experienced stress episodes than did PHT individuals, but these stress events ended sooner. Similarity in stress experiences between the two Jomon samples and differences between the HKJ and PHT are found. These findings are important for two reasons. First, stress experiences of foraging populations differ markedly and cannot be generalized by subsistence strategy alone. Second, due to significant differences in episode duration, stress experiences cannot be understood using prevalence comparisons alone. Am J Phys Anthropol 152:230–238, 2013. © 2013 Wiley Periodicals, Inc.